2020
DOI: 10.1155/2020/8254909
|View full text |Cite
|
Sign up to set email alerts
|

The Role and Potential Pathogenic Mechanism of Particulate Matter in Childhood Asthma: A Review and Perspective

Abstract: Asthma, the most common chronic respiratory disease in children, affects numerous people worldwide. Accumulating evidence suggests that exposure to high levels of particulate matter (PM), either acutely or chronically, is associated with the exacerbation and incidence of pediatric asthma. However, the detailed pathogenic mechanisms by which PM contributes to the incidence of asthma remain largely unknown. In this short review, we summarize studies of relationships between PM and pediatric asthma and recent adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 84 publications
0
16
0
Order By: Relevance
“…145 It has also been suggested that mucus hypersecretion is an underlying cause of hypoxia in COVID-19 patients. 146 Interestingly, PM exposure can suppress mucociliary clearance and promotes mucus hypersecretion, 147,148 although whether effects of PM exposure on mucus production and mucociliary clearance affect SARS-CoV-2 infection and COVID-19 pathogenesis is unclear. Pollutant exposure also decreases levels of various antioxidants in the respiratory tract-lining fluid and tissues, increasing the susceptibility to further oxidative damage mediated by inflammation and/or continued pollutant exposure.…”
Section: How Can Air Pollution Contribute To Sars-cov-2 Infection Andmentioning
confidence: 99%
“…145 It has also been suggested that mucus hypersecretion is an underlying cause of hypoxia in COVID-19 patients. 146 Interestingly, PM exposure can suppress mucociliary clearance and promotes mucus hypersecretion, 147,148 although whether effects of PM exposure on mucus production and mucociliary clearance affect SARS-CoV-2 infection and COVID-19 pathogenesis is unclear. Pollutant exposure also decreases levels of various antioxidants in the respiratory tract-lining fluid and tissues, increasing the susceptibility to further oxidative damage mediated by inflammation and/or continued pollutant exposure.…”
Section: How Can Air Pollution Contribute To Sars-cov-2 Infection Andmentioning
confidence: 99%
“…A number of environmental factors have been reported to affect the development and severity of asthma, including outdoor air pollutants (e.g., particulates, ozone), indoor irritants, and agents such as environmental tobacco smoke. However, it can be argued that the most significant inhaled agents that modulate the development of respiratory allergy and asthma are biologics [1]. Particulate matter PM10 exposure during pregnancy was reported as an association with the risk of a new diagnosis of asthma in recent studies, which becomes an additional risk factor predicting development of various inflammatory conditions future in life [2].…”
Section: Discussionmentioning
confidence: 99%
“…Based on "aerodynamic equivalent diameter" (AED), PM is categorized into three classes, including coarse particles or PM 10 (ranging from 2.5 to 10 µm); fine particles or PM 2.5 (smaller than 2.5 µm); ultrafine particles or PM 0.1 (UFP, smaller than 0.1 µm) [34,35]. Regardless of the PM composition, differently sized PMs are expected to have different particle velocities for settling in the respiratory tract [36]. Generally, PM contains various chemical constituents, including inorganic ions (e.g., sulfates, nitrates, ammonium, sodium, potassium, calcium, magnesium, and chloride), heavy metals (including cadmium, copper, nickel, vanadium, and zinc), black carbon, and organic compounds (e.g., polycyclic aromatic hydrocarbons, and polyaromatic hydrocarbons (PAHs)) [28,37,38].…”
Section: Source and Characteristics Of Pmmentioning
confidence: 99%
“…Nevertheless, information regarding the pathophysiological aspects of these diseases and their association with innate immunity remains scarce. Various factors could influence the incidence, severity, and pathogenesis of these diseases, including the period of exposure, exposure duration, particle size and components of PM, ethnicity, age, and gender [36].…”
Section: Inflammatory Insultsmentioning
confidence: 99%